Impact of Urban Expansion on Migratory Birds in the Lagos Wetlands: Breeding Habits and Population Dynamics - Amina Yusuf (Studies in Social Science & Humanities, 2024)
This research delves into the complex interactions between urban expansion and migratory bird populations in the Lagos wetlands, specifically examining how changes in urban landscapes influence breeding habits and population dynamics. The rapid and extensive urbanization in Lagos has resulted in considerable habitat fragmentation and environmental degradation, leading to significant disruptions in the ecological functions vital for the sustenance of migratory bird species. This study conducts a thorough analysis of existing conservation measures, assessing their effectiveness and identifying gaps in current practices. Building on this analysis, the research proposes a suite of integrated strategies for sustainable urban planning that emphasizes wildlife preservation. These strategies include the development of green infrastructure, the establishment of ecological corridors, enhanced community involvement in conservation efforts, and the integration of robust environmental policies into urban planning frameworks. The study underscores the critical need for a holistic and scalable approach to urban planning, one that effectively balances human development with the preservation of biodiversity. The findings advocate for a multi-faceted response to urban impacts, suggesting that while current conservation efforts provide a foundation, they require significant expansion and reinforcement to safeguard the migratory bird populations and maintain the ecological health of the Lagos wetlands in the face of ongoing urban challenges.